2023
DOI: 10.1111/php.13829
|View full text |Cite
|
Sign up to set email alerts
|

Can l‐ascorbic acid and trans‐resveratrol protect HaCaT cells from fine particulate matter toxicity?

Krystian Mokrzyński,
Olga Krzysztyńska‐Kuleta,
Mateusz Wojtala
et al.

Abstract: Continuous exposure of human skin to air pollution can result in a range of undesirable skin conditions. In our recent study, UV and visible light were found to increase cytotoxicity of fine particulate matter (PM2.5) against human keratinocytes. Since it is impossible to avoid exposure of human skin to PM2.5, effective strategies are needed to reduce their damaging effects. l‐ascorbic acid and resveratrol were tested as potential topical agents against pollution‐related skin impairment. Although these agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
2
0
1
Order By: Relevance
“…Trans-resveratrol (TRE), a naturally occurring polyphenol found in high concentrations in grape seeds and skins, has been the subject of extensive research because of its potent antioxidant, anti-inflammatory, and antipsychotic characteristics [115]. Studies have shown that TRE can effectively scavenge PM-generated free radicals and mono-linear oxygen 2.5, reduce cell death and prevent oxidative damage to HaCaT cells, and protect HaCaT cells against the dark and light induced toxicity of PM2.5 [116].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Trans-resveratrol (TRE), a naturally occurring polyphenol found in high concentrations in grape seeds and skins, has been the subject of extensive research because of its potent antioxidant, anti-inflammatory, and antipsychotic characteristics [115]. Studies have shown that TRE can effectively scavenge PM-generated free radicals and mono-linear oxygen 2.5, reduce cell death and prevent oxidative damage to HaCaT cells, and protect HaCaT cells against the dark and light induced toxicity of PM2.5 [116].…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Trans-resveratrol (TRE), a naturally occurring polyphenol found in high concentrations in grape seeds and skins, has been the subject of extensive research because of its potent antioxidant, anti-inflammatory, and antipsychotic characteristics [ 132 ]. Studies have shown that TRE can effectively scavenge PM-generated free radicals and mono-linear oxygen 2.5, reduce cell death, and prevent oxidative damage to HaCaT cells, and protect HaCaT cells against the dark and light induced toxicity of PM2.5 [ 59 ].…”
Section: Role and Mechanisms Of Polyphenols In The Treatment Of Nervo...mentioning
confidence: 99%
“…Cele mai recente date de literatură susțin rezultatele descrise de noi. Astfel, Mokrzyński și colaboratorii au folosit testul DPPH ca parte a unei abordări complexe dedicate evaluării impactului AA și tRes asupra leziunii oxidative mediate de materia particulată (PM 2.5 ) asupra celulelor HaCaT (linia celulară de keratinocite epidermice umane), ca model de epidermă [24]. A fost descoperit, că atât AA, cât și tRes, dar mai ales atunci când sunt aplicați în combinație, pot proteja celulele HaCaT împotriva toxicității UV și a luminii vizibile induse de PM 2.5 prin eliminarea eficientă a radicalilor liberi și a oxigenului singlet produs de PM 2.5 .…”
Section: Sistemul Tres-aaunclassified